Wicked games [videorecording (DVD)] - Spang, Christine; Shenefelt, Michael; Matzer, Jody (Screen Media Films, 2023)
When Harley joins her new boyfriend for a long Halloween weekend at his country estate, they're invaded by a band of masked freaks and forced to play a Wicked Game. To the intruders' unpleasant surprise, Harley's hard-boiled history has endowed her with a bag of tricks that give the game a surprise ending.